2010
DOI: 10.1074/jbc.m110.121459
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism Involving Coordinated Regulation of Nuclear Levels and Acetylation of NF-YA and Bcl6 Activates RGS4 Transcription

Abstract: Neuronally enriched RGS4 plays a critical role attenuating G protein signaling in brain, although the mechanisms regulating RGS4 expression are unknown. Here we describe a novel mechanism for transcriptional activation of RGS4 in neuron-like PC6 cells, where RGS4 is markedly induced during confluence-induced growth arrest. Transcriptional activation of RGS4 in confluent PC6 cells was accompanied by impaired G i/o -dependent MAPK activation. In the human RGS4 gene promoter, we identified three phylogenetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…However, the regulatory mechanism of Rgs4 expression has not been well understood. We and others have demonstrated that Rgs4 expression is transcriptionally regulated [6], [38], [64][67]. We have cloned and characterized the promoter region of rabbit Rgs4 [38].…”
Section: Discussionmentioning
confidence: 98%
“…However, the regulatory mechanism of Rgs4 expression has not been well understood. We and others have demonstrated that Rgs4 expression is transcriptionally regulated [6], [38], [64][67]. We have cloned and characterized the promoter region of rabbit Rgs4 [38].…”
Section: Discussionmentioning
confidence: 98%
“…Our data provide information regarding a previously unknown molecular mechanism in which RGS4 promotes NSCLC cell proliferation by regulating miR-16 expression. The expression of miR-16 is downregulated in NSCLC tissue samples and cell lines as well as in other malignancies 35,37,40–50. In NSCLC, miR-16 suppresses tumor development by inhibiting cell proliferation and promoting apoptosis 29,41.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has also been reported to control neurogenesis (Tiberi et al, 2012). Interestingly, BCL6 binds to the promoter of RGS4 to repress its transcription (Yang et al, 2010). RGS4 is a candidate vulnerability gene that was found to be down-regulated in previous studies in SCZ (Bowden et al, 2007;Erdely et al, 2006;Levitt et al, 2006;Mirnics et al, 2001).…”
Section: Idmentioning
confidence: 93%